(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2025)
Gambling in Malaysia is frowned upon due to its potentially harmful effects on society. Nevertheless, the same industry also generates income through taxes. Most Malaysian lottery companies still resort to various methods to remain relevant. Past research indicates how Malaysian lottery companies rely on supporting charitable deeds and metaphors to promote their positive images. This article examines how lottery gambling in Malaysia creates a space that advocates heteropatriarchy: a system that favours heterosexual males over cisgender females and minorities of cisgender origin through archetypes and stereotypes. Using Jungian and social theory approaches, the paper investigates how the family patriarchs are constantly portrayed through the everyday hero archetype, while women and other minorities are stereotyped as weaklings and dependents. Ten newsletters reporting lottery winners and companies’ activities released by Sports Toto and Da Ma Cai in the past three years reveal how archetypes and stereotypes distinguish family patriarchs from their dependents. The findings demonstrate the portrayal of heterosexual men in a positive light and inadvertently highlight that, for these lottery companies, creating a space that advocates heteropatriarchy is crucial for their relevance and their brand image. It also communicates that women can be exploited through stereotypes used to promote brand images.